MAKNA NYANYIAN MA’KAARUYEN DALAM KEHIDUPAN MASYARAKAT MINAHASA - Wibowo, Markus (Institut Agama Kristen Negeri Manado, 2020)
This research is a meaning of Ma'kaaruyen; a traditional musical work of art originating from Minahasa. Ma'kaaruyen is assumed to be one of the arts that reflects the life of the Minahasa community. Through a musicalological approach to the analysis of musical elements and the analysis of the texts of the Ma'kaaruyen song, meaning is found that integrates with the values ​​of the life of the Minahasa community. In the musical meaning it is known that Ma'kaaruyen has musical elements that form this song included in the category of melancholy singing, so that with lyrics or without lyrics this song is a melancholy song that is able to influence the soul. Ma'kaaruyen's extramusical meanings of the musical elements refer to the nature and character of traditional Minahasa community life, including: rhythm, melody, intervals, harmony, texture, and song form. The elements of music in Ma'kaaruyen are a reflection of the character and nature of traditional Minahasa society, which is associated with simplicity, calmness, gentleness, cooperation (mapalus), and mutual affection. Ma'kaaruyen's extramusical meaning from lyrics is that Ma'kaaruyen is a song that conveys religious messages, advice, affection, and expressions of heart (lamentations and regrets).